Prevalence and genetic diversity of Aeromonas veronii isolated from aquaculture systems in the Poyang Lake area, China - Xu, Xiandong; Fu, Huiyun; Wan, Guoyuan; Huang, Jiangfeng; Zhou, Zhiyong; Rao, Yi; Liu, Lihui; Wen, Chungen (Frontiers in Microbiology, 2022)
The area around Poyang Lake is the main aquaculture area in Jiangxi Province, China, and an important supply base for fresh freshwater aquatic products. Aquaculture in the Poyang Lake area is severely threatened by diseases caused by bacterial pathogens, and Aeromonas veronii has been the main pathogen in recent years. In this paper, ERIC-PCR genotyping, virulence gene and antimicrobial resistance gene detection, and drug susceptibility tests were carried out on 46 A. veronii strains isolated from aquaculture systems in the Poyang Lake area from 2016 to 2020. The results showed that the A. veronii strains had high genetic diversity in the Poyang Lake area, and 46 strains produced 36 ERIC genotypes. There were no geographical and temporal differences in the cluster analysis results and no dominant clones. All of the 13 kinds of virulence genes were detected, and all strains had multiple virulence factors, containing 2 or more virulence genes, with a maximum of 12 kinds of virulence genes. Among the 22 kinds of antimicrobial resistance genes selected, 15 were detected; 97.8% of the strains contained 2 or more antimicrobial resistance genes, with a maximum of 9 kinds of antimicrobial resistance genes. Drug susceptibility tests showed that some strains were resistant to a variety of traditionally effective drugs for Aeromomas, such as enrofloxacin and florfenicol. This study provides a reference for exploring the impact of aquaculture in the Poyang Lake area on public health.